The Nandu or Nyakap System: Subak Local Wisdom in The Realm if Profit Sharing to Improve The Welfare of Farmers - Ayuni, Ni Made Sri; Widnyani, Ni Made; Budiasni, Ni Wayan Novi (Lembaga Riset dan Inovasi Al-Matani, 2022)
This research uses a qualitative approach. Data collection techniques used in this study were in the form of interviews supported by documentation and observation, which were selected as respondents or informants were 6 key informants consisting of 3 smallholders, 3 landowners, and 3 supporting informants namely the management of Subak Yeh Taluh which consists of the Chairperson, Secretary and Treasurer. The data validity checking technique used is to use triangulation, namely triangulation techniques and source triangulation, while data analysis techniques consist of data collection, data reduction, data presentation and drawing conclusions. Based on the results of the process that has been processed shows that nandu activities are capable of subak Yeh Taluh Penarukan carried out in three models, namely mixed, for five, and for two where all three are considered capable of helping the welfare of farmers with the management of land with a certain area as the main support for increasing income and farmers' welfare. The purpose of this study was to find out how profit sharing models were applied to the Nandu system on the Subak Yeh Taluh Penarukan Buleleng and its effectitive qualitative approach